Age and Outcomes in Hip Arthroscopy for Femoroacetabular Impingement: A Comparison Across 3 Age Groups. Issue 1 (January 2021) - Lin, Lawrence J.; Akpinar, Berkcan; Bloom, David A.; Youm, Thomas
Background: Limited evidence exists concerning the effect of age on hip arthroscopy outcomes for femoroacetabular impingement (FAI). Purpose/Hypothesis: The purpose was to investigate patient-reported outcomes (PROs) and clinical failure rates across various age groups in patients undergoing hip arthroscopy for FAI. We hypothesized that older patients would experience lower improvements in PROs and higher clinical failure rates. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 109 of 130 eligible consecutive patients underwent hip arthroscopy for FAI with a minimum 5-year follow-up. Patients were stratified into 3 groups for comparison (ages 15-34, 35-50, and 51-75 years). Clinical survival rates to revision surgery or total hip arthroplasty (THA) were determined by Kaplan-Meier analysis, and PROs were assessed using analysis of variance. Regression analysis was used to determine factors associated with clinical failure and ΔPROs from baseline to 5 years. Results: The 5-year survival-to-revision rate was 71% (survival time, 69.2 months; 95% CI, 62.8 to 75.5 months). A significant difference in survival to THA was found between groups ( P = .030). Being in the older group versus the young and middle-aged groups predicted increased risk of THA conversion (hazard ratio, 5.7; 95% CI, 1.1 to 28.6; P = .035). Overall modified Harris Hip Score (mHHS) and Nonarthritic Hip Score (NAHS) improved from baseline to 5 years (mHHS, P < .001; NAHS, P < .001). Body mass index (mHHS: beta, −1.2; 95% CI, −2.2 to −0.3; P = .013; NAHS: beta, −1.6; 95% CI, −2.6 to −0.5; P = .005) and baseline PROs (mHHS: beta, −0.8; 95% CI, −1.1 to −0.4; P < .001; NAHS: beta, −0.7; 95% CI, −1.1 to −0.4; P < .001) were predictive of 5-year ΔPROs. A decrease was seen in minimal clinically important difference rates in middle-aged ( P = .011) and old ( P = .030) groups from 6-month to 5-year outcomes. Conclusion: Although hip arthroscopy for FAI yielded improvements in PROs regardless of age, middle-aged and older patients experienced greater declines in clinical outcomes over time than younger patients. Older patients remain good candidates for arthroscopy despite a greater risk for conversion to THA.